On the Klein-Gordon oscillators in Eddington-inspired Born-Infeld gravity global monopole spacetime and a Wu-Yang magnetic monopole - Mustafa, Omar; Soares, A. R.; Pereira, C. F. S.; Vitoria, R. L. L. (Springer, 2024)
We consider Klein-Gordon (KG) particles in a global monopole (GM) spacetime within Eddington-inspired Born-Infeld gravity (EiBI-gravity) and in a Wu-Yang magnetic monopole (WYMM). We discuss a set of KG-oscillators in such spacetime settings. We propose a textbook power series expansion for the KG radial wave function that allows us to retrieve the exact energy levels for KG-oscillators in a GM spacetime and a WYMM without EiBI-gravity. We, moreover, report some conditionally exact, closed form, energy levels (through some parametric correlations) for KG-oscillators in a GM spacetime and a WYMM within EiBI-gravity, and for massless KG-oscillators in a GM spacetime and a WYMM within EiBI-gravity under the influence of a Coulomb plus linear Lorentz scalar potential. We report the effects of the Eddington parameter k, GM-parameter alpha, WYMM strength sigma, KG-oscillators' frequency Omega, and the coupling parameters of the Coulomb plus linear Lorentz scalar potential, on the spectroscopic structure of the KG-oscillators at hand. Such effects are studied over a vast range of the radial quantum number n(r) >= 0 and include energy levels clustering at l sigma l>>1 (i.e., extreme EiBI-gravity), and at |sigma|>>1 (i.e., extreme WYMM strength).
Keywords: Lorentz Symmetry Violation; Gravitational-Field; Thermodynamic Properties; Dirac Oscillator; Topological Defects; Equation; Particle; Subject; Strings; Frame